2018
DOI: 10.1038/aps.2017.196
|View full text |Cite
|
Sign up to set email alerts
|

Circular noncoding RNAs as potential therapies and circulating biomarkers for cardiovascular diseases

Abstract: Recent advancements in genome-wide analyses and RNA-sequencing technologies led to the discovery of small noncoding RNAs, such as microRNAs (miRs), as well as both linear long noncoding RNAs (lncRNAs) and circular long noncoding RNAs (circRNAs). The importance of miRs and lncRNAs in the treatment, prognosis and diagnosis of cardiovascular diseases (CVDs) has been extensively reported. We also previously reviewed their implications in therapies and as biomarkers for CVDs. More recently, circRNAs have also emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
63
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 81 publications
1
63
0
4
Order By: Relevance
“…In addition, circRNAs are more stable and abundant than miRNAs in serum and other body fluids, and in extracellular vesicles (13). Therefore, circRNAs are ideal candidates as potential disease biomarkers and therapeutic targets (14). However, the mechanisms underlying the roles of circRNAs in cardiomyocyte death induced by anoxia/reoxygenation (A/R) or ischemia/reperfusion (I/R) injury are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, circRNAs are more stable and abundant than miRNAs in serum and other body fluids, and in extracellular vesicles (13). Therefore, circRNAs are ideal candidates as potential disease biomarkers and therapeutic targets (14). However, the mechanisms underlying the roles of circRNAs in cardiomyocyte death induced by anoxia/reoxygenation (A/R) or ischemia/reperfusion (I/R) injury are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, abnormal circRNA expressions have been demonstrated in various cardiovascular diseases and cancers, which are related to vascular dysfunction. [6][7][8] Knockdown of cZNF609, which is highly enriched in endothelial cells, diminished retinal vessel loss and inhibited pathological angiogenesis in vivo. 9 CircRNA USP1 (circ-USP1, also known as hsa_circ_0000080 according to circBase), which is located at chr1p31, is derived from the back-splicing of exon 6-8 of ubiquitin-specific peptidase 1 (USP1) gene.…”
mentioning
confidence: 99%
“…Growing evidence has demonstrated that miRNAs play important roles in the regulation of development, differentiation, proliferation, and apoptosis [5, 6]. Notably, it has been reported that several miRNAs contribute to the development and progression of cardiac fibrosis [7-9]. For example, up-regulation of miR-21 [10], miR-34a and miR-93 [11] promoted the development of cardiac fibrosis, whereas overexpression of miR-133, and miR-590 [12], together with down-regulation of miR-23 [13], miR-29 [14], miR-101 [15] and miR-132 [16], suppressed the fibrotic responses of cardiac fibroblasts (CFs).…”
Section: Introductionmentioning
confidence: 99%